Biodegradation of Petroleum Hydrocarbons by Bacillus spp.: A Review (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2018)
This mini review aims to provide an overview of petroleum hydrocarbons degradation by Bacillus species. The first half of the scientific assessment is focusing on the impact of usage of petroleum hydrocarbons such as diesel fuels towards organisms and the surrounding environments. The other section of the literature collection discusses on the microbial remediation of this recalcitrant compounds by microbial species with special highlight on the genus Bacillus. This short evaluation will improve our present comprehension of bacterial degradation of petroleum hydrocarbons and their respective derivatives while providing an insight on the role of Bacillus species in microbial remediation communities.
Keywords: Biodegradation, petroleum hydrocarbons, bacteria, Bacillus spp.